Particulate matter (pm), respiratory symptoms and peak expiratory flow rate among workers at two bus terminals - Zulkefli, Nurul Zulainie (Universiti Sains Malaysia, 2015)
Workers at bus terminal are exposed to harmful particulate matter (PM) from busexhausts through inhalation. A cross sectional study was conducted to determine the association of PM with respiratory symptoms and peak expiratory flow rate (PEFR) among workers at two bus terminals; Kota Bharu and Pekeliling bus terminals. Eighty seven healthy workers were recruited as respondent from purposive sampling. Dustmate (Turnkey, England) and Humidity alert II Hygro-Thermometer (Extech, USA) were used to collect the PM, temperature, relative humidity and dew point, respectively. Environmental monitoring were conducted eight hours daily for fortnight at each locations. Reported respiratory symptoms were gathered by interview using a British Medical Research Council (MRC), UK questionnaires. The lung function status was measured using peak flow meter (Philips, Netherlands) to evaluate if there is a degree of airflow obstruction in the respondents’ airways. PM25and PM| were higher at Pekeliling bus terminal [PM25=18.4 (IQR: 14.2-24.5) pg/m3; PMi=6.95 (IQR: 4.9-9.6) pg/m3] compared to Kota Bharu bus terminal [PM2.s=14.4 (IQR: 9.2-24.1) pg/m3; PMi=5.41 (IQR: 2.8-10) pg/m3)] (p= 0.001). There was significant correlation between PM (PM2.s and PMi) with meteorological variables (temperature, humidity and dew point) (p=0.001). The commonest symptoms reported among the subjects was wheezing while in dusty place (65.5%, n=57). This study also found no significant different of PEFR reading between subjects from both locations (p>0.05). Besides, there is no correlation between PEFR readings with PM (p>0.05). Moderate correlation was found between PEFR reading with height (p=0.001, r=0.469) and body surface area (BSA) (p=0.001, r=0.446). Separated bus platform from ticket counter, retail shops and food stalls are the best way to reduce PM exposure among the workers.